Deciphering the Antibacterial Role of Peptide From Bacillus subtilis subsp. spizizenii Ba49 Against Staphylococcus aureus - Ramita Taggar; Sanpreet Singh; Vijayender Bhalla; Mani Shankar Bhattacharyya; Debendra K. Sahoo; Debendra K. Sahoo (Frontiers in Microbiology, 2021)
An increase in antibiotic resistance has led to escalating the need for the development of alternate therapy. Antimicrobial peptides (AMPs) are at the forefront of replacing conventional antibiotics, showing slower development of drug resistance, antibiofilm activity, and the ability to modulate the host immune response. The ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) pathogens that jeopardize most conventional antibiotics are known to be involved in severe respiratory tract, bloodstream, urinary tract, soft tissue, and skin infections. Among them, S. aureus is an insidious microbe and developed resistance against conventional antibiotics. In the present study, an AMP (named as peptide-Ba49) isolated from Bacillus subtilis subsp. spizizenii strain from Allium cepa (the common onion) exhibited strong antibacterial efficacy against S. aureus ATCC 25923. The mode of action of this peptide-Ba49 on S. aureus was deciphered through various sensitive probes, i.e., DiSC3 (5) and H2DCFDA, suggesting the peptide-Ba49 to be acting upon through change in membrane potential and by triggering the production of reactive oxygen species (ROS). This induced disruption of the cell membrane was further supported by morphological studies using scanning electron microscopy (SEM). Investigations on a possible post-antibiotic effect (PAE) of peptide-Ba49 showed prolonged PAE against S. aureus. Furthermore, the peptide-Ba49 prevented the formation of S. aureus biofilm at low concentration and showed its potential to degrade the mature biofilm of S. aureus. The peptide-Ba49 also exhibited intracellular killing potential against S. aureus ATCC 25923 in the macrophage cells, and moreover, peptide-Ba49 was found to bolster the fibroblast cell migration in the scratch assay at low concentration, exhibiting a wound healing efficacy of this peptide. These studies demonstrated that peptide-Ba49 isolated from the strain B. subtilis subsp. spizizenii could be a therapeutic candidate to combat the pathogenic S. aureus infections.